Factores criminológicos interculturales en el delito de peculado financiero - Jerez Caisabanda, Carmen María (2025)
This scientific article provides a legal analysis of the intercultural criminological factors that influence the crime of financial embezzlement in the Nativa and Salasaca savings and credit cooperatives during the period 2012-2015. The main objective is to identify and understand how interculturality and other criminological factors influence the actors who commit financial embezzlement. To achieve this, qualitative methods were employed, including interviews with judges, public defenders and prosecutors, as well as a bibliographic and normative analysis of the Constitution. The results indicated that the financial offenders in these cases did not present the typical profile of common criminals; they tended to maintain a respectable appearance and avoided violent behavior. The main suspects were often absent from the hearings, suggesting strategies to evade justice. Through the legal analysis, it became evident that the criminological factors that influenced the actors to commit financial embezzlement were: ambition, lack of ethics, manipulation, ignorance, culture and economic status. These elements were aggravated by the access and total control over accounting and financial operations, which allowed the undue manipulation of funds, the coverage of deficits with irregular financial movements and the lack of adequate accounting records. It also underlines the need for a specialized and coordinated approach to address financial graft, highlighting the importance of cross-cultural justice and the improvement of internal controls and transparency in financial cooperatives.